Ecology And Taxonomy of Mangifera Species (Anacardiaceae) in the 50-HA Plot of Pasoh Forest Reserve, Peninsular Malaysia - Linatoc, Alona Cuevas (1999)
The study was conducted at the 50-ha plot of Pasoh Forest Reserve, Negeri Sembilan, Peninsular Malaysia to assess the ecological distribution of Mangifera and to solve some taxonomic problems on doubtful species by clearly circumscribing the limits among taxa by using morphological, anatomical and DNA sequences evidences. Thirteen Mangifera taxa were recorded to a total population of 1,202 stems. Mangifera quadrifida is the most abundant with 275 stems, followed by M foetida with 208 stems. The least is M swintonioides with only two trees, both more than 10 cm dbh. Mangifera quadrifida var. longipetiolata has 16 trees all less than 10 cm dbh. The common mango, M indica has only 80 stems. Mangifera griffithii has the most number of trees with dbh exceeding 10 cm, thereby giving the highest estimates in terms of basal area (0. 045 m²ha⁻¹), volume (0. 63 m³ha⁻¹), and above ground biomass (0. 51 tha⁻¹). A total of 163 dead trees were recorded since the initial survey in 1985. High mortality (85%) was found to be trees of less than 10 cm dbh. Mortality of seedlings was primarily caused by burrowing and nest building by wild pigs, while death of big trees was caused by termite attack. Taxonomic review of the genus was carried out exploiting morphological and anatomical characters. However, due to unavailability of reproductive characters throughout the entire course of the study, investigation was carried out making use of vegetative characters alone. Given all the morphological and anatomical evidences, the genus can be divided into two subgenera viz. Limus and Mangifera. This subdivision is further supported by examining the molecular phylogeny of 13 Mangifera taxa using nucleotide sequences of the intergenic spacer region between trnL-trnF of the chloroplast DNA. In the phylogenetic study, two major clades were formed from the monophyletic tree. It is noted that M subsessilifolia, a species incertae was in a clade with M lagenifera and M superba of the subgenus Limus. The second clade on the other hand was composed of species belonging to the subgenus Mangifera except for M foetida, which was classified under subgenus Limus. However, M macrocarpa of subgenus Limus formed a singleton as did M gracilipes of subgenus Mangifera. The divergence of the genus Mangifera is apparent from the heterogeneous feature of the subgenera. Further analysis of other molecular markers from different genes or genomes and consideration of other species of wild mangoes are necessary to infer a stronger phylogenetic analysis of this taxon.